Drivers of female entrepreneurship in Asian economies: a panel data analysis - Firoz Alam; Amaan Ullah; Nawab Ali Khan; Mohd Saeem Khan; Mohd Yasir Arafat; Imran Saleem (Cogent Business & Management, 2024)
The number of women venturing into small-scale businesses has increased with the increasing popularity of entrepreneurship. Though it has recently been acknowledged that entrepreneurship is a `gendered phenomenon', entrepreneurship research over previous few decades has mostly concentrated on the traits and psychology of entrepreneurs. Furthermore, although researchers and policymakers have recently documented the role of females in the field of entrepreneurship, their contributions are yet to be recognized. Hence, we aim to explicitly analyze the scenario of female entrepreneurship, recognizing variations between men and women in the context of entrepreneurial endeavors. The literature investigating the factors that drive their success or hinders their growth is still in a nascent stage. Hence, there is a need to explore and understand the determinants of entrepreneurship particularly the female entrepreneurship. Given this backdrop, this study aims to identify the most significant factors that influence female entrepreneurs' behavior while entering entrepreneurship. We analyzed data from the Global Entrepreneurship Monitor (GEM) database from 2001 to 2020 using panel data analysis to address the research problem. Our empirical study shows that in all the selected Asian economies, more women enter entrepreneurship because of the opportunities it offers rather than necessity. In conclusion, we provide several suggestions for encouraging female entrepreneurship that can substantially contribute to the growth of the Asian economies under study.
Keywords: 650; Female entrepreneurship; necessity and opportunity-based entrepreneurship; socio-economic factors; GEM database; panel data analysis